Assessing ICT Competency in Teachers In Relation to Requirements of the Professional Standard for Teachers - Avdeyeva S.M; Nikulicheva N.V; Khapayeva S.S; Zaichkina O.I (Moscow State University of Psychology and Education, 2017)
The paper describes conceptual approaches to the assessment of ICT competency in teachers following requirements of the professional standard for teachers. It provides an analysis of the existing approaches. ICT competency is considered as a teacher's ability to plan, organize and implement teaching/learning activity in an educational context according to the requirements of the Federal State Educational Standard in General Education, to actively participate in the development of an educational organization, and to continue to develop professionally. The paper outlines the authors' approach to designing test frameworks for ICT competency assessment. The materials of this paper represent the outcomes of a research carried out by the Federal Institute for Education Development on the topic "Conceptual Approaches to Assessing ICT Competency in Teachers with Regard to the Professional Standard". This paper was written as a part of work carried out for the Ministry of Education and Science № 27.302.2016/НМ on the topic «Conceptual Approaches to Assessing ICT Competency in Teachers with Regard to the Professional Standard».